Kekuatan Alat Bukti Akta Otentik Dalam Pembuktian Perkara Perdata - Komang Ayuk Septianingsih; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi Dewi (Jurnal Analogi Hukum, 2020)
Abstract—Authentic deed is a deed in the form determined by law, made by or in front of the general employees in power for that place where the deed is made, and as for general officials who are authorized to make authentic deeds, namely a Notary or PPAT. The main issue is how the power of authentic deeds is proven in civil cases and how the notary's responsibility for authentic deeds is null and void. The research method used is a type of normative legal research. While the problem approach which is the approach to the conceptual approach problem, is done by examining the views that occur in the development of legal science and the legislative approach, carried out by examining the legal aspects that have a relationship with the legal issues examined. The value of the power of outward proof, the strength of formal proof and the strength of material proof are those covered by an authentic deed. Responsible for negligence and mistakes in the contents of the deed made before him are the responsibility of the notary. In the world of notoriety there are 2 types of sanctions, namely civil sanctions and administrative sanctions. The sanction is imposed on the notary if the deed he has made is an error or a violation of the law, besides that it can also make the deed null and void.